Serum Human Epididymis Protein 4 as a Novel Biomarker in Identifying Patients With Interstitial Lung Disease in Rheumatoid Arthritis - Liang, Liu; Chen, Jiali; Di, Chun; Zhan, Minghua; Bao, Huizhang; Xia, Changsheng; Fan, Chunhong; Liu, Yudong (Frontiers in Medicine, 2021)
Objective: Human epididymis protein 4 (HE4) have been implicated in the pulmonary involvements. We aimed to investigate the clinical utility of HE4 in clinical stratification in patients with rheumatoid arthritis (RA). Methods: This study included a discovery cohort comprising 70 RA patients and 64 healthy controls (HCs), and a validation cohort comprising 98 RA patients and 75 HCs. Human epididymis protein 4 were determined by electrochemical luminescence analyzer. Results: The levels of HE4 were significantly elevated in patients with RA compared to HCs. The positive rates of HE4 in patients with RA and HCs were 50.0% and 0, respectively, in the discovery cohort and 53.1 and 1.3%, respectively, in the validation cohort. When RA patients were subgrouped according to HE4 status, HE4-positive group displayed higher prevalence of interstitial lung disease (ILD) compared to HE4-negative group (28.6 vs. 11.4% in discovery cohort and 57.7 vs. 8.7% in the validation cohort). A positive correlation between the levels of HE4 with the degree of lung impairment was identified. Receiver operating curve (ROC) analysis revealed an optimal cut-off value of 104.3 pmol/L in HE4 for distinguishing RA-ILD from RA-non ILD with the areas under the curve (AUC) of 0.790. Multivariate logistic regression analysis illustrated that high levels of HE4 independently identified patients with RA-ILD (OR, 9.080, p < 0.001). Conclusion: Our findings showed a novel role of HE4 in RA risk stratification, suggest that introducing HE4 to the current RA test panel may serve as an indicator in identifying RA patients for further RA-ILD workups, such as high-resolution computed tomography (HRCT).